The Spatiality of Prostitution in Budapest During the Austro-Hungarian Monarchy - TŐTŐS, Áron (Studia Universitatis Babeș-Bolyai Historia, 2025)
This study examines the spatial structure and social embeddedness of prostitution in Budapest during the Austro-Hungarian Monarchy, with particular focus on the Dualist era. Drawing on an extensive topographic database compiled from police records, prison registries, and archival maps, it documents the activities of 13,891 individuals and the locations of 2,615 prostitution-related establishments across 559 streets. The findings challenge the concept of a single, segregated red-light district: prostitutional institutions – brothels, private apartments, and entertainment venues – were dispersed throughout the city, albeit with notable concentrations in Terézváros, Erzsébetváros, Józsefváros, and the Inner City. Spatial patterns were shaped by urban morphology, population density, transport networks, and regulatory frameworks, while also reflecting social stratification and moral geography. The analysis operates at multiple spatial scales, from district-level distributions to individual buildings, and applies network analysis to identify 45 key hubs that structured the city’s prostitutional system. The results highlight both the historical continuity of certain prostitution sites and the adaptability of the sex industry to urban modernization, revealing its integration into Budapest’s economic, social, and cultural life. Rezumat: Acest studiu examinează structura spațială și înrădăcinarea socială a prostituției în Budapesta în timpul Monarhiei austro-ungare, cu accent deosebit pe epoca dualistă. Bazându-se pe o bază extinsă de date topografice, compilată din înregistrări ale poliției, registre ale închisorilor și hărți de arhivă, acest studiu documentează activitățile a 13.891 de persoane și locațiile a 2.615 unități legate de prostituție pe 559 de străzi. Constatările contestă conceptul unui singur cartier roșu segregat: instituțiile de prostituție - bordeluri, apartamente private și locuri de divertisment - erau dispersate în tot orașul, deși cu concentrații notabile în Terézváros, Erzsébetváros, Józsefváros și în centrul orașului. Modelele spațiale au fost modelate de morfologia urbană, densitatea populației, rețelele de transport și cadrele de reglementare, reflectând în același timp stratificarea socială și geografia morală. Analiza operează la scări spațiale multiple, de la distribuții la nivel de district la clădiri individuale, și aplică analiza rețelei pentru a identifica 45 de centre cheie care au structurat sistemul de prostituție al orașului. Rezultatele evidențiază atât continuitatea istorică a anumitor locuri de prostituție, cât și adaptabilitatea industriei sexului la modernizarea urbană, dezvăluind integrarea acesteia în viața economică, socială și culturală a Budapestei. Cuvinte-cheie: Istorie urbană, prostituție, spațiu urban, istorie spațială, Budapesta, Monarhia Austro-Ungară, geografie socială, analiză de rețea